2001
DOI: 10.1046/j.1365-2044.2001.01980.x
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy and safety of nefopam vs. propacetamol following hepatic resection*

Abstract: SummaryIn order to compare the morphine-sparing effect, analgesic efficacy and tolerance of nefopam and propacetamol given at their highest recommended doses, 120 patients undergoing elective hepatic resection were randomly assigned to receive postoperative intravenous patient-controlled analgesia with morphine alone, or in combination with nefopam (20 mg. . Analgesia was superior in the nefopam group despite the lower morphine consumption. Adverse effects were comparable in the three groups, except for signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
102
6
9

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 19 publications
11
102
6
9
Order By: Relevance
“…5 Studies have consistently demonstrated a 30-40% decrease in postoperative opioid consumption when nefopam is used following abdominal or orthopaedic surgery. 6,7 Unlike nonsteroidal anti-inflammatory drugs, nefopam has no effect on platelet function, 8 and (in contrast to opioids) does not increase the risk of respiratory depression. 9 In addition, nefopam has been shown to result in decreased morphine consumption when used as a coanalgesic following abdominal surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Studies have consistently demonstrated a 30-40% decrease in postoperative opioid consumption when nefopam is used following abdominal or orthopaedic surgery. 6,7 Unlike nonsteroidal anti-inflammatory drugs, nefopam has no effect on platelet function, 8 and (in contrast to opioids) does not increase the risk of respiratory depression. 9 In addition, nefopam has been shown to result in decreased morphine consumption when used as a coanalgesic following abdominal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast with others who reported that sweating was more common in patients given nefopam than propacetemol or morphine. 7 All patients in the present study were admitted to the ICU following surgery and some were infused with inotropic agents or vasopressors, according to need. As these sympathomimetic drugs can mask the effects of nefopam, 23 the vital signs, respiratory effort and hepatorenal functions of every patient in the present study were closely observed while they were in the ICU.…”
mentioning
confidence: 99%
“…Thus, it is necessary to seek alternatives. Nefopam is a centrally acting non-opioid analgesic (Piercey and Schroeder 1981;Durrieu et al 2007) that has been mainly used to treat cancer pain, visceral smooth muscle cramps and postoperative pain (Mimoz et al 2001). Nefopam has a particularly good effect on reducing postoperative chronic pain and improving postoperative pain management (Laboureyras et al 2009).…”
mentioning
confidence: 99%
“…На сегодняшний день не существует общепри нятого и безопасного алгоритма анестезиологиче ского пособия для ведения пациентов с ЦП [21]. Ре комендуют тщательное титрование лекарственных средств как для анестезии, так и для периопераци онного обез боливания.…”
Section: клиническая проблемаunclassified